2010
DOI: 10.1111/j.1526-4610.2009.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Epicrania Fugax: Ten New Cases and Therapeutic Results

Abstract: This description reinforces the proposal of EF as a new headache variant or a new headache syndrome. Anesthetic blockades, carbamazepine, gabapentin, and lamotrigine have been apparently effective in individual patients. Further observations and therapeutic trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 29 publications
(32 reference statements)
4
47
0
Order By: Relevance
“…We registered all the demographic and clinical data of these patients. We included in the analysis characteristics of 6 patients previously described [2]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We registered all the demographic and clinical data of these patients. We included in the analysis characteristics of 6 patients previously described [2]. …”
Section: Methodsmentioning
confidence: 99%
“…To this first series, 15 new patients with the same clinical features have been added, so reinforcing the proposal of EF as a new headache variant or a new headache syndrome [2–4]. Recently, two patients who fulfilled all the characteristics for EF except the direction of radiation have been reported.…”
Section: Introductionmentioning
confidence: 92%
“…Epicrania fugax (EF) has been recently classified as a primary headache in the appendix of the International Classification of Headache Disorders, 3rd edition, beta version . Since EF was first proposed as a new syndrome by Pareja et al in 2008, more than 60 cases have been reported . The essential feature of EF is the occurrence of dynamic painful paroxysms, with a quick and ample movement through the surface of one side of the head.…”
mentioning
confidence: 99%
“…Initial descriptions depicted a unilateral pain spreading from posterior cranial areas to the ipsilateral anterior scalp, following a linear or zigzag trajectory – that is the classical forward EF 1,5. Later on, a backward EF – with pain radiating from frontal areas toward the posterior scalp – was also described, with no demographic or clinical differences between both variants 6–8.…”
Section: Introductionmentioning
confidence: 99%